Correction of sunken upper eyelids using the triple plane technique with hyaluronic acid fillers - Yun Sik Sung; Won Tak Choi (Journal of Cosmetic Medicine, 2025)
Background: Sunken upper eyelids, characterized by volume deficiency, cause aesthetic and functional issues, such as an aged appearance and ocular discomfort. Objective: This study aimed to evaluate the effectiveness and safety of the triple plane technique using hyaluronic acid (HA) fillers tailored for three anatomical layers (retro-orbicularis oculi fat [ROOF], supraorbital fat, and dermal layer) in correcting sunken upper eyelids. Methods: In this retrospective cohort study, 357 patients treated from January 2021 to June 2024 were classified by severity (grades 1-4). The triple plane technique involved injecting high-viscosity cross-linked HA filler into the deep ROOF layer, mixed cross-linked and non-cross-linked fillers into the intermediate layer, and fine-particle HA filler with polydeoxyribonucleotide into the dermal layer. Results: Outcomes were assessed based on visual improvement in eyelid hollowness. All Grade 1 patients (n=100) achieved complete normalization. In Grade 2 patients (n=140), 23.6% improved by two grades (to normal), and 76.4% improved by one grade. In Grade 3 (n=62), 35.5% improved by two grades and 64.5% by one grade. For Grade 4 (n=55), 21.8% improved by three grades, 18.2% by two grades, and 60.0% by one grade. No severe complications were observed, and patient satisfaction was high. Conclusion: In conclusion, the triple plane technique with HA fillers provided effective, safe, and aesthetically pleasing results across varying severities of sunken upper eyelids. Further research is warranted to evaluate its long-term efficacy and sustainability.